(untitled) (Al-Aasar, 2025)
This study explores the lived experiences of visually impaired people (VIP) in Pakistan by identifying the challenges they face during outdoor navigation and exploring the strategies they employ to overcome those navigation barriers. Nineteen participants were recruited through snowball sampling technique and in-depth interviews were conducted regarding their navigational experiences. The Interpretative Phenomenological Analysis (Smith & Osborn, 2015) highlights participants’ emotional experiences and their perceptions of accessibility, along with the social, cultural and attitudinal barriers that affect their navigational experiences. The findings reveal that inadequate infrastructure, lack of mobility trainings, limited access to/familiarity with assistive technologies and societal attitudes not only influence mobility and independence of VIPs but also perpetuate discrimination and exclusion. By understanding the navigational challenges faced by VIPs, the study contributes to the development of more accessible and inclusive urban environments in Pakistan.